2014
DOI: 10.1103/physreve.90.032310
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric-spectroscopy approach to ferrofluid nanoparticle clustering induced by an external electric field

Abstract: An experimental study of magnetic colloidal particles cluster formation induced by an external electric field in a ferrofluid based on transformer oil is presented. Using frequency domain isothermal dielectric spectroscopy, we study the influence of a test cell electrode separation distance on a low-frequency relaxation process. We consider the relaxation process to be associated with an electric double layer polarization taking place on the particle surface. It has been found that the relaxation maximum consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(14 citation statements)
references
References 33 publications
1
13
0
Order By: Relevance
“…Similar effects in mineral oil-based FFs induced by an external electric field have been reported just recently [10,11]. For that purpose, the method of dielectric spectroscopy and in situ small angle neutron scattering were applied.…”
Section: Introductionmentioning
confidence: 52%
See 1 more Smart Citation
“…Similar effects in mineral oil-based FFs induced by an external electric field have been reported just recently [10,11]. For that purpose, the method of dielectric spectroscopy and in situ small angle neutron scattering were applied.…”
Section: Introductionmentioning
confidence: 52%
“…Before the appearance of the visible EHD flow, one can assume that the effective polarization of MNPs and their interface (surfactant and surrounding counter ions [11]) takes place during this time, leading to the induced electric dipole-dipole interactions supported by Van der Waals and magnetic interactions (as the MNPs possess permanent magnetic moments). This behavior happens on the nanoscale, far from the resolution of the optical microscopy.…”
Section: Resultsmentioning
confidence: 99%
“…To analyze this spectrum we take into account that the transformer oil shows constant permittivity (ε = 2.1) in the whole frequency range. As the known conductivity and permittivity values of the sample constituents determine the appearance of the MaxwellWagner relaxation at much higher frequencies, we associate the low frequency process with the ion impurity polarization taking place on the SNP surfaces [10,11], following the famous Schwarz polarization model.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, it was shown that similar assemblies can be induced by electric fields. Especially ferrofluids based on insulating liquids are characterized by a high dielectric contrast between the particles and the base liquid, which results in the effective particle polarization and dielectrophoresis leading to the particle assembling [13,14]. On the other hand, this type of ferrofluids is of increasing interest due to their potential application in high voltage engineering [15].…”
Section: Introductionmentioning
confidence: 99%